Characterization systems for RFID applications - Jordão, Marina Daniela da Cruz (2015)
This dissertation has the collaboration of the Telecommunications Institute with National Instruments, in order to develop solutions for characterization and measurement for RF-DC converters. These characterization solutions are intended to ensure optimization of this type of circuit, which is the basis of Wireless Power Transmission and Electromagnetic Energy Harvesting systems. It is intended to use LabVIEW code and the PXI modules from NI with the goal of extrapolating these measurement systems to read and measure the RFID Tags. Therefore, this dissertation is focused on RFID characterization using the LabVIEW, in other words, RFID reader.